The Influence of Flanking Secondary Structures on Amino Acid Content and Typical Lengths of 3/10 Helices - Khrustalev, Vladislav Victorovich (Hindawi Publishing Corporation, 2014)
We used 3D structures of a highly redundant set of bacterial proteins encoded by genes of high, average, and low GC-content. Four types of connecting bridges—regions situated between any of two major elements of secondary structure (alpha helices and beta strands)—containing a pure random coil were compared with connecting bridges containing 3/10 helices. We included discovered trends in the original “VVTAK Connecting Bridges” algorithm, which is able to predict more probable conformation for a given connecting bridge. The highest number of significant differences in amino acid usage was found between 3/10 helices containing bridges connecting two beta strands (they have increased Phe, Tyr, Met, Ile, Leu, Val, and His usages but decreased usages of Asp, Asn, Gly, and Pro) and those without 3/10 helices. The typical (most common) length of 3/10 helices situated between two beta strands and between beta strand and alpha helix is equal to 5 amino acid residues. The preferred length of 3/10 helices situated between alpha helix and beta strand is equal to 3 residues. For 3/10 helices situated between two alpha helices, both lengths (3 and 5 amino acid residues) are typical.